2012
DOI: 10.1097/fjc.0b013e3182580b75
|View full text |Cite
|
Sign up to set email alerts
|

Sarin Causes Autonomic Imbalance and Cardiomyopathy

Abstract: Sarin, a lethal chemical nerve agent, may be a causative factor in multifactorial syndrome implicated in the Gulf War and Tokyo terrorist attacks. Although a high dose results in seizure and death, low-dose exposure may lead to autonomic imbalance and chronic cardiac pathologies. In this study, echocardiography and electrocardiography were used to examine the late-onset effects of a low-dose sarin on cardiac structure and function in mice. Adrenal corticosterone and tyrosine hydroxylase mRNA levels were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(42 reference statements)
1
6
0
Order By: Relevance
“…Left ventricular function and geometry was assessed as previously described [ 36 ]. Briefly, mice underwent echocardiographic assessment using an ACUSON Sequoia ™ C512 Ultrasound System (Siemens) with a 15-MHz linear array transducer.…”
Section: Methodsmentioning
confidence: 99%
“…Left ventricular function and geometry was assessed as previously described [ 36 ]. Briefly, mice underwent echocardiographic assessment using an ACUSON Sequoia ™ C512 Ultrasound System (Siemens) with a 15-MHz linear array transducer.…”
Section: Methodsmentioning
confidence: 99%
“…A few of these studies have investigated the potential outcomes of low-dose, sub-lethal exposure(s) to sarin or sarin surrogates alone in relationship to GWI symptomology. While subclinical inhalation of sarin has been demonstrated to be capable of producing signs of immunosuppression, such as reduced T-cell responses and reduced corticosterone levels ( Henderson et al, 2001 ; Kalra et al, 2002 ), as well as autonomic imbalance and cardiomyopathy ( Shewale et al, 2012 ), these studies do not directly correlate with the neuroimmune dysfunction hypothesis for GWI. However, repeated, low-dose exposure to the sarin surrogate diisopropyl fluorophosphate (DFP) has been shown to instigate depression, cognitive impairment, and neuronal damage ( Phillips and Deshpande, 2016 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The long term decrease in both serum corticosterone and plasma adrenocorticotropic levels indicates that hypothalamus–pituitary–adrenal axis suppression likely occurred due to sarin exposure, although the mechanism of action is not entirely clear (Peña-Philippides et al 2007). Shewale et al (2012) also demonstrated altered HPA responsiveness and reduced corticosterone levels following sarin exposure and postulates that the cause of this alteration was an autonomic imbalance.…”
Section: Organophosphates-induced Endocrine Disruption (Opied)mentioning
confidence: 95%